Multi-layer co-extrusion POE photovoltaic packaging adhesive film and preparation method thereof

Through the three-layer co-extrusion method combined with EVA and POE resin and added polypropylene fibers, a multi-layer co-extruded POE photovoltaic packaging film was prepared, which solved the problem of delamination and additive migration of the photovoltaic packaging film under high temperature and high humidity conditions, and improved the performance and component life of the film.

CN120484709APending Publication Date: 2025-08-15PETROCHINA CO LTD

Patent Information

Application Number
CN202410120685.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-01-29
Publication Date
2025-08-15

AI Technical Summary

Technical Problem

The existing photovoltaic packaging films are prone to delamination and additive migration under high temperature and high humidity conditions, resulting in a decrease in light transmittance and attenuation of battery output power. The EVA film has poor anti-ultraviolet aging ability, while the POE film is not strongly bonded to glass, and string deviation is prone to occur during lamination.

Method used

A three-layer coextrusion method is adopted, using the EVA layer as the upper and lower layers and the POE layer as the intermediate layer, and polypropylene fiber is added to the POE layer, and a multi-layer coextruded POE photovoltaic packaging film is prepared by blending and combining with crosslinking agents, antioxidants, coupling agents, etc.

Benefits of technology

It improves the tensile strength, low-temperature impact strength and water vapor barrier properties of the adhesive film, extends the service life of photovoltaic modules, solves the problems of delamination and additive migration, and improves the operating reliability and cost-effectiveness of the power station.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120484709A_ABST
    Figure CN120484709A_ABST
Patent Text Reader

Abstract

The invention provides a multi-layer co-extrusion POE (Polyolefin Elastomer) photovoltaic packaging adhesive film and a preparation method thereof. The photovoltaic packaging adhesive film comprises three layers, namely an upper layer, a middle layer and a lower layer, the upper layer and the lower layer are both EVA layers, and the middle layer is a POE layer; wherein the content of vinyl acetate in the EVA layer is 30-35%, the density of EVA resin is 0.920-0.948 g / cm < 3 >, and the MFI is 1.5-15 g / 10 min; the content of octene in the POE resin in the POE layer is 20-35%, the density is 0.875-0.890 g / cm < 3 >, and the MFI is 4-6 g / 10 min. The multi-layer co-extrusion POE photovoltaic packaging adhesive film prepared by a three-layer co-extrusion method combines the advantages of EVA and POE resin, and can avoid delamination and auxiliary agent migration.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a multi-layer co-extruded POE photovoltaic encapsulation adhesive film and a preparation method thereof, belonging to the technical field of multi-layer film materials. Background Art

[0002] Photovoltaic modules require a suitable film to seal and protect the cells, interconnects, and backsheets. EVA film is the most common film, primarily composed of ethylene-vinyl acetate copolymer (EVA), along with small amounts of crosslinkers, co-crosslinkers, antioxidants, and other functional additives. EVA is produced by copolymerizing two monomers. While the ethylene chain is relatively stable, the vinyl acetate segments are susceptible to hydrolysis and photothermal aging reactions under high temperature and humidity conditions. This can cause EVA degradation, resulting in bubbles, delamination, and yellowing. This reduces light transmittance, module power generation, and shortens module lifespan. Finding an alternative to EVA resin for use in photovoltaic encapsulation has become a pressing issue.

[0003] Polyolefin elastomer (POE) refers to a thermoplastic elastomer produced by in-situ polymerization of ethylene and α-olefins using a metallocene catalyst. The crystalline regions (resin phase) of the polyethylene segments act as physical crosslinking points, resulting in certain plastic properties and crystallinity, a narrow relative molecular weight, and a low density. The addition of a certain amount of α-olefins (1-butene, 1-hexene, 1-octene) weakens the crystalline regions of the polyethylene segments, resulting in excellent weathering and UV aging resistance, excellent heat and low-temperature resistance, a wide operating temperature range, good light transmittance, excellent electrical insulation properties, high cost-effectiveness, and easy processing. POE, as it is commonly referred to, refers to ethylene-octene copolymer elastomers with an octene mass fraction greater than 20%. Its good compatibility with polyolefins and high cost-effectiveness have led to its widespread application in automotive, footwear, wire and cable, packaging, polymer modification, and medical applications. However, POE, a non-polar polymer, suffers from relatively low strength and adhesion, and its unsatisfactory mechanical properties hinder its application in photovoltaic encapsulation films.

[0004] The encapsulation films used in the photovoltaic industry are currently developing towards long lifespan, high efficiency, and low cost. Currently, the market primarily consists of two main types of encapsulation films: EVA and POE. EVA films offer advantages such as low processing temperature, strong impact resistance, high transmittance, good melt flowability, excellent melt adhesion, and a relatively low price. However, they suffer from poor resistance to UV and heat aging. Furthermore, due to their high water vapor transmission rate, EVA internally hydrolyzes into acetate ions, which induces metal cation migration and positive charge accumulation on the battery chip surface, leading to potential-induced degradation (PID), which seriously affects battery output power. While POE films offer significant advantages in terms of UV and heat aging resistance and PID resistance, they have low polarity and weak adhesion to glass or backsheets, making them susceptible to cross-linking during lamination. Furthermore, POE resins have poor compatibility with polar additives, making them prone to bubble formation during subsequent processing and use.

[0005] CN103289582B discloses a cross-linked POE encapsulation film for solar photovoltaic modules. This encapsulation film is primarily composed of a silane-grafted POE resin, along with additives such as a crosslinker, a crosslinking aid, and an anti-aging agent. The preparation method involves first preparing the silane-grafted POE resin, then uniformly mixing the grafted POE with the additives and casting the resulting film through an extruder. After vacuuming and heat lamination, the film can achieve a crosslinking degree exceeding 70%.

[0006] CN109810639A discloses a POE film, a photovoltaic encapsulation material with potential induced attenuation. The film uses an internal crosslinking agent containing both double bonds and amide groups, which has high reactivity. In addition, the internal crosslinking agent is an olefin monomer, which has good compatibility with polyolefin elastomers and high crosslinking density after the reaction. The POE film can be used on the front, back or both sides of the battery cell to prevent water vapor from eroding the front of the battery cell, effectively preventing Na in the glass from eroding. + , K + , Ca 2+ The positive ions migrate to the surface of the battery cell, thus making the photovoltaic modules in the power station have anti-PID performance; on the other hand, the combination of organic peroxide cross-linking agent, internal cross-linking agent and auxiliary cross-linking agent makes the residual heat enthalpy of the cross-linked film very low, reducing the generation of impurities, further improving the anti-PID performance of the module and ensuring the normal output power of the photovoltaic module.

[0007] On the other hand, EPE film, a new packaging material created by co-extruding EVA and POE, retains the ease of lamination and high adhesion of EVA through composite modification, while also offering the high barrier and weather resistance of polyolefins. However, EPE film suffers from issues such as delamination of EVA and POE, migration of additives in the POE layer, and uneven thickness distribution of the POE layer, hindering its widespread application. Summary of the Invention

[0008] To solve the above technical problems, the present invention aims to provide a multi-layer co-extruded POE photovoltaic encapsulation film and a preparation method thereof. A multi-layer co-extruded POE photovoltaic encapsulation film is prepared by a three-layer co-extrusion method, combining the advantages of EVA and POE resins, and adding polypropylene fiber to the POE layer.

[0009] To achieve the above object, the present invention provides a multi-layer co-extruded POE photovoltaic encapsulation film, wherein the photovoltaic encapsulation film comprises three layers, namely an upper layer, a middle layer and a lower layer; the upper layer and the lower layer are both EVA layers, and the middle layer is a POE layer; wherein the EVA resin used in the EVA layer has a vinyl acetate content of 30-35%, and a density of the EVA resin of 0.920-0.948 g / cm 3 , MFI is 1.5-15g / 10min;

[0010] The raw materials of the POE layer include: 100 parts by weight of POE resin, 5-30 parts by weight of polypropylene fiber, 0.1-5 parts by weight of a cross-linking agent, 0.01-2 parts by weight of a coupling agent and 0.01-0.8 parts by weight of an antioxidant;

[0011] The octene content of the POE resin is 20-35% (preferably 30%), and the density of the POE resin is 0.875-0.890 g / cm 3 , MFI is 4-6 g / 10 min (preferably 5 g / 10 min).

[0012] The content of monomer octene in POE resin has a great influence on the density of the product. The higher the octene content, the lower the density of the product. Since low-density POE products are prepared into films, the volume resistivity of the product increases and the anti-PID performance is poor. Therefore, the present invention uses high-density POE products.

[0013] According to a specific embodiment of the present invention, preferably, the POE layer is prepared by melt-plasticizing the raw materials of the POE layer, co-extruding, casting, embossing, and cooling to form a film.

[0014] In some specific embodiments, preferably, the added amount of the polypropylene fiber is 10-20 parts by weight, the added amount of the crosslinking agent is 0.1-1 part by weight, the added amount of the coupling agent is 0.05-0.1 part by weight, and the added amount of the antioxidant is 0.01-0.05 part by weight.

[0015] According to a specific embodiment of the present invention, preferably, the polypropylene fiber has a length of 1-60 μm, a thermal conductivity of 0.25-100 W / m·k, a relative density of 0.90-0.92, and an intrinsic viscosity of 1.3-3.

[0016] Polypropylene fiber (PP) has high strength, relatively high temperature stability, can withstand moisture, and can also withstand various acid and alkali corrosion well. Therefore, compared with other fibers, polypropylene fiber is relatively more resistant to ultraviolet rays and can maintain a longer service life under sunlight, but is prone to problems such as discoloration and aging. In addition, because the apparent shear viscosity of polypropylene fiber depends on temperature similarly to that of POE, polypropylene fiber has particularly good compatibility and dispersibility in POE, and can form a POE / PP island structure. It is easy to obtain a smaller dispersed phase particle size and a narrower particle size distribution in the POE matrix, thus having a significant toughening effect.

[0017] In some specific embodiments, preferably, the polypropylene fiber has a length of 40 μm, a thermal conductivity of 20-50 W / m·k, and an intrinsic viscosity of 1.5.

[0018] According to a specific embodiment of the present invention, preferably, the cross-linking agent includes: tetraisocyanate, propylene diamine, polyethylene glycol, polypropylene glycol, trimethylolpropane, trimethylolethane, polypropylene glycol glycidyl ether, p-toluenesulfonic acid, p-toluenesulfonyl chloride, diacrylate-1,4-butylene glycol ester, dimethacrylate ethylene glycol ester, butyl acrylate, dicumyl peroxide, bis-2,4-dichlorobenzoyl peroxide, 2,2-bis(tert-amyl peroxy)-butane, tert-amyl peroxybenzoate, aluminum isopropoxide, zinc acetate, titanium acetylacetonate, acrylic acid, hydroxyethyl acrylate, hydroxypropyl acrylate, methacrylic acid, hydroxyethyl methacrylate, hydroxypropyl methacrylate, divinylbenzene, N-hydroxymethyl acrylamide, diacetone acrylamide, or a combination of two or more thereof. More preferably, the cross-linking agent is a mixture of tert-amyl peroxybenzoate and 2,2-bis(tert-amyl peroxy)-butane in a mass ratio of 1:1.5.

[0019] According to a specific embodiment of the present invention, preferably, the coupling agent includes γ-aminopropyltriethoxysilane, γ-(2,3-epoxypropoxy)propyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane, n-octyltriethoxysilane, vinyltriethoxysilane, vinyltrimethoxysilane, vinyl-tri(2-methoxyethoxy)silane, isopropyl dioleyloxy (dioctylphosphoacyloxy) titanate, isopropyl trioleyloxy titanate, isopropoxy tris(dodecylbenzenesulfonyloxy) titanate, isopropoxy tris(dioctylpyrophosphate) titanate, bis(dioctylpyrophosphate) ethylene titanate, an ammonium salt aqueous solution of bis(dioctylpyrophosphate) ethylene titanate, tetraisopropyl di(dioctyl phosphite) titanate, isopropyl tristearate titanate, and methacrylate silane, or a combination of two or more thereof. More preferably, the coupling agent is a mixture of γ-aminopropyltriethoxysilane and methacrylate silane, with a mass ratio of 1:1.5.

[0020] According to a specific embodiment of the present invention, preferably, the antioxidant used in the POE layer includes one or a combination of two or more of tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]pentaerythritol, β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, N,N'-hexane-1,6-diylbis[3-(3,5-di-tert-butyl-4-hydroxyphenylpropionamide)], 3,3',3',5,5',5'-hexa-tert-butyl-α,α',α'-(mesitylene-2,4,6-triyl)tri-p-cresol, and 2,6-di-tert-butyl-4-[4,6-bis(octylthio)-1,3,5-triazin-2-ylamino]phenol. More preferably, the antioxidant used in the POE layer is tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]pentaerythritol.

[0021] According to a specific embodiment of the present invention, preferably, the thickness of the photovoltaic encapsulation film is 0.1-1 mm.

[0022] According to a specific embodiment of the present invention, preferably, the thickness ratio of the upper layer, the middle layer and the lower layer is 0.7-1:1.8-2.1:0.7-1.

[0023] The present invention also provides a method for preparing the above-mentioned multi-layer co-extruded POE photovoltaic encapsulation film, wherein the preparation method comprises:

[0024] (1) POE resin and polypropylene fiber are uniformly mixed, and then extruded into granules at 180-250° C., and the obtained granules are uniformly mixed with a cross-linking agent, a coupling agent and an antioxidant to obtain the raw material of the middle layer;

[0025] (2) mixing 100 parts by weight of EVA resin, 0.1-2 parts by weight of antioxidant, and 1-5 parts by weight of light stabilizer to obtain raw materials for the upper layer and the lower layer;

[0026] (3) The raw materials of the upper layer, the middle layer and the lower layer are stirred and mixed in a mixing kettle at 45°C, added into respective feed barrels, melted and plasticized at a temperature of 180-250°C through an extruder, and fused at the co-extrusion grinding head at the flute of the extruder. After cast or calendering, embossing, cooling, pulling and winding, a multi-layer co-extruded POE photovoltaic encapsulation film is obtained.

[0027] According to a specific embodiment of the present invention, preferably, the light stabilizer includes one or a combination of two or more of bis(1-octyloxy-2,2,6,6-tetramethyl-4-piperidinyl) sebacate, poly-{[6-[(1,1,3,3-tetramethylbutyl)-imino]-1,3,5-triazine-2,4-diyl][2-(2,2,6,6-tetramethylpiperidinyl)-nitro-hexamethylene-[4-(2,2,6,6-tetramethylpiperidinyl)-nitro]], bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate, and poly(4-hydroxy-2,2,6,6-tetramethyl-1-piperidinethanol) succinate.

[0028] According to a specific embodiment of the present invention, preferably, in step (2), the antioxidant used in the EVA layer is a mixture of pentaerythritol distearate diphosphite and 1,3,5-tris(4-tert-butyl-3-hydroxy-2,6-dimethylphenyl)-1,3,5-triazine-2,4,6-(1H,3H,5H)-trione, with a mass ratio of 1:1-2.

[0029] Compared with the prior art, the present invention has the following beneficial effects:

[0030] (1) The multi-layer co-extruded POE photovoltaic encapsulation film prepared by the present invention has the characteristics of high tensile strength, high low-temperature impact strength, excellent water vapor barrier rate and long service life; by blending polypropylene fiber with POE resin, and then mixing it with a cross-linking agent, an antioxidant, a coupling agent, etc. in a suitable proportion and process parameters, the multi-layer co-extruded POE photovoltaic encapsulation film prepared can better ensure the long-term service life of photovoltaic modules than pure EVA film, thereby increasing the income of power stations.

[0031] (2) Introducing POE resin as the middle layer, and utilizing the amorphous area of POE resin can increase its absorption effect on additives, thereby improving the slip problem; at the same time, using high-density POE resin as the middle layer and adopting a three-layer co-extrusion structure can not only solve the compatibility problem between resins and avoid delamination and additive migration, but also, under the condition of the same film thickness, after introducing POE resin, it can take into account both low cost and high reliability. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 This is a scanning electron microscope image of the pellets in Example 1. DETAILED DESCRIPTION

[0033] In order to have a clearer understanding of the technical features, objectives and beneficial effects of the present invention, the technical solution of the present invention is now described in detail below, but it should not be understood as limiting the scope of implementation of the present invention.

[0034] The sources of the raw materials in the embodiments of the present invention, including raw material names, specifications, manufacturers, etc. are shown in Table 1:

[0035] Table 1. Raw material names, specifications and manufacturers of the examples

[0036]

[0037]

[0038] Example 1

[0039] This embodiment provides a method for preparing a multi-layer co-extruded POE photovoltaic encapsulation film, which includes the following steps:

[0040] (1) 100 parts by weight of POE resin and 30 parts by weight of polypropylene fiber were mixed uniformly, and then extruded into granules at 190° C., and the obtained granules were mixed uniformly with 0.5 parts by weight of a cross-linking agent, 0.1 parts by weight of a coupling agent, and 0.05 parts by weight of an antioxidant to obtain the raw material for the middle layer.

[0041] like Figure 1 As shown, the pellet product has a POE / PP island structure as analyzed by electron microscopy, and this result proves that perfect compatibility is achieved.

[0042] Among them, the middle layer is prepared using the following raw materials:

[0043] The product density of POE resin is 0.875g / cm 3 , octene content is 30%, MFI is 5.0;

[0044] The length of polypropylene fiber is 40 μm, the thermal conductivity is 20 W / m·k, and the relative density is 0.92 g / cm 3 , intrinsic viscosity is 3;

[0045] The crosslinking agent is a mixture of tert-amyl peroxybenzoate and 2,2-bis(tert-amylperoxy)-butane, with a mass ratio of 1:1.5;

[0046] The coupling agent is a mixture of γ-aminopropyltriethoxysilane and methacrylate silane in a mass ratio of 1:1.5;

[0047] The antioxidant is pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate].

[0048] (2) 100 parts by weight of EVA resin, 2 parts by weight of antioxidant, and 3.2 parts by weight of light stabilizer were mixed to obtain raw materials for the upper layer and the lower layer.

[0049] The EVA resin has a vinyl acetate content of 30% and a density of 0.948 g / cm 3 , MFI is 15g / 10min; the antioxidant is a mixture of distearate pentaerythritol diphosphite and 1,3,5-tris(4-tert-butyl-3-hydroxy-2,6-dimethylphenyl)-1,3,5-triazine-2,4,6-(1H,3H,5H)-trione, with a mass ratio of 1:1.5; the light stabilizer is bis(1-octyloxy-2,2,6,6-tetramethyl-4-piperidinyl) sebacate.

[0050] (3) The raw materials of the upper layer, the middle layer and the lower layer are stirred and mixed in a mixing kettle at 45°C, added to their respective feed barrels, melted and plasticized at a temperature of 210°C through an extruder, and fused at the co-extrusion grinding head at the extruder flute. After cast or calendering, embossing, cooling, pulling and winding, a multi-layer co-extruded POE photovoltaic encapsulation film is obtained.

[0051] The thickness of the photovoltaic encapsulation film is 0.60 mm, and the thickness ratio of the upper layer, the middle layer and the lower layer is 1:2:1.

[0052] Example 2

[0053] This embodiment provides a method for preparing a multi-layer co-extruded POE photovoltaic encapsulation film, which includes the following steps:

[0054] (1) 100 parts by weight of POE resin and 5 parts by weight of polypropylene fiber were mixed uniformly, and then extruded into granules at 210° C. The obtained granules were mixed uniformly with 0.5 parts by weight of a cross-linking agent, 2 parts by weight of a coupling agent, and 0.8 parts by weight of an antioxidant to obtain the raw material for the middle layer.

[0055] Among them, the middle layer is prepared using the following raw materials:

[0056] The product density of POE resin is 0.875g / cm 3 , octene content is 20%, MFI is 5.0;

[0057] The length of the polypropylene fiber is 40 μm, the thermal conductivity is 0.25 W / m·k, and the relative density is 0.92 g / cm3 , intrinsic viscosity is 3;

[0058] The crosslinking agent is a mixture of tert-amyl peroxybenzoate and 2,2-bis(tert-amylperoxy)-butane, with a mass ratio of 1:1.5;

[0059] The coupling agent is a mixture of γ-aminopropyltriethoxysilane and methacrylate silane in a mass ratio of 1:1.5;

[0060] The antioxidant is pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate].

[0061] (2) 100 parts by weight of EVA resin, 2 parts by weight of antioxidant, and 3.2 parts by weight of light stabilizer were mixed to obtain raw materials for the upper layer and the lower layer.

[0062] The EVA resin has a vinyl acetate content of 30% and a density of 0.948 g / cm 3 , MFI is 15g / 10min; the antioxidant is a mixture of distearate pentaerythritol diphosphite and 1,3,5-tris(4-tert-butyl-3-hydroxy-2,6-dimethylphenyl)-1,3,5-triazine-2,4,6-(1H,3H,5H)-trione, with a mass ratio of 1:1.5; the light stabilizer is bis(1-octyloxy-2,2,6,6-tetramethyl-4-piperidinyl) sebacate.

[0063] (3) The raw materials of the upper layer, the middle layer and the lower layer are stirred and mixed in a mixing kettle at 45°C, added to their respective feed barrels, melted and plasticized at a temperature of 210°C through an extruder, and fused at the co-extrusion grinding head at the extruder flute. After cast or calendering, embossing, cooling, pulling and winding, a multi-layer co-extruded POE photovoltaic encapsulation film is obtained.

[0064] The thickness of the photovoltaic encapsulation film is 0.60 mm, and the thickness ratio of the upper layer, the middle layer and the lower layer is 1:2:1.

[0065] Comparative Example 1

[0066] This comparative example provides a method for preparing a single-layer EVA photovoltaic encapsulation film, which comprises the following steps:

[0067] 100 parts by weight of EVA resin, 2 parts by weight of antioxidant, and 3.2 parts by weight of light stabilizer are stirred and mixed in a mixing kettle at 45°C, melt-plasticized at a temperature of 210°C through an extruder, extruded through an extruder head at the flute mouth of the extruder, and subjected to cast or calendering molding, embossing, cooling, pulling, and winding to obtain an EVA photovoltaic encapsulation film.

[0068] The EVA resin has a vinyl acetate content of 30% and a density of 0.948 g / cm 3 , MFI is 15g / 10min; the antioxidant is a mixture of distearate pentaerythritol diphosphite and 1,3,5-tris(4-tert-butyl-3-hydroxy-2,6-dimethylphenyl)-1,3,5-triazine-2,4,6-(1H,3H,5H)-trione, with a mass ratio of 1:1.5; the light stabilizer is bis(1-octyloxy-2,2,6,6-tetramethyl-4-piperidinyl) sebacate.

[0069] The thickness of the photovoltaic encapsulation film is 0.60 mm.

[0070] The performance of the photovoltaic encapsulation films prepared in Examples 1-2 and Comparative Example 1 was tested below, and the relevant experimental results are shown in Table 2.

[0071] Table 2. Performance test results of photovoltaic encapsulation films prepared in Examples 1-2 and Comparative Example 1

[0072]

[0073] From the experimental results in Table 2, it can be seen that the multilayer co-extruded photovoltaic encapsulation film prepared in Examples 1-2 has higher tensile strength and low-temperature impact strength than the single-layer photovoltaic encapsulation film in Comparative Example 1, and better barrier properties to water vapor.

[0074] Comparative Example 2

[0075] This comparative example provides a method for preparing an enhanced POE photovoltaic encapsulation film, which comprises the following steps:

[0076] 100 parts by weight of POE resin, 10 parts by weight of polyethylene fiber, 10 parts by weight of reinforcing resin, and 3 parts by weight of compatibilizer are mixed evenly, and then added with 0.02 parts by weight of coupling agent, 0.05 parts by weight of cross-linking agent, 0.02 parts by weight of antioxidant, 0.02 parts by weight of UV absorber, 0.12 parts of high-efficiency degassing agent, and 30 parts of thermal conductive powder, and put into an extruder for mixing. The extruder temperature is 140°C, and the film is formed through casting, embossing, and cooling.

[0077] Among them, the thermal conductive powder is nano zinc oxide;

[0078] The length of polyethylene fiber is 0.5-40μm, the thermal conductivity is 80-100W / m·k, and the molecular weight of polyethylene is above 1 million;

[0079] The reinforcing resin is a mixture of reinforcing resin polybutene and ethylene propylene rubber, with a mass ratio of 1:1;

[0080] The compatibilizer is a mixture of POE grafted methacrylate copolymer, polypropylene grafted glycidyl methacrylate copolymer and EPDM grafted maleic anhydride copolymer, with a mass ratio of 1:1.2:2;

[0081] The coupling agent is a mixture of γ-aminopropyltriethoxysilane and methacrylate silane in a mass ratio of 1:1;

[0082] The crosslinking agent is a mixture of tert-amyl peroxybenzoate and 2,2-bis(tert-amylperoxy)-butane in a mass ratio of 1:1.2;

[0083] The antioxidant is a mixture of pentaerythritol distearate diphosphite and 1,3,5-tris(4-tert-butyl-3-hydroxy-2,6-dimethylphenyl)-1,3,5-triazine-2,4,6-(1H,3H,5H)-trione, with a mass ratio of 1:1;

[0084] The high-efficiency degassing agent is MPP620 (MPI, American Micro Powder Company).

[0085] Comparative Example 3

[0086] This comparative example provides a method for preparing an enhanced POE photovoltaic encapsulation film, which comprises the following steps:

[0087] 100 parts by weight of POE resin, 12 parts by weight of polyethylene fiber, 12 parts by weight of reinforcing resin, and 4 parts by weight of compatibilizer are mixed evenly, and then added with 40.03 parts by weight of coupling agent, 0.8 parts by weight of cross-linking agent, 0.03 parts by weight of antioxidant, 0.03 parts by weight of UV absorber, 0.13 parts of high-efficiency degassing agent, and 32 parts of thermal conductive powder, and put into an extruder for mixing. The extruder temperature is 140°C, and the film is formed through casting, embossing, and cooling.

[0088] The thermal conductive powder is a mixture of nano zinc oxide and aluminum nitride, with a mass ratio of 2:1.

[0089] The length of polyethylene fiber is 0.5-40μm, the thermal conductivity is 80-100W / m·k, and the molecular weight of polyethylene is above 1 million;

[0090] The reinforcing resin is a mixture of reinforcing resin polybutene and ethylene propylene rubber, with a mass ratio of 1:1;

[0091] The compatibilizer is a mixture of POE grafted methacrylate copolymer, polypropylene grafted glycidyl methacrylate copolymer and EPDM grafted maleic anhydride copolymer, with a mass ratio of 1:1.2:2.3;

[0092] The coupling agent is a mixture of γ-aminopropyltriethoxysilane and methacrylate silane in a mass ratio of 1:1;

[0093] The crosslinking agent is a mixture of tert-amyl peroxybenzoate and 2,2-bis(tert-amylperoxy)-butane in a mass ratio of 1:1.2;

[0094] The antioxidant is a mixture of pentaerythritol distearate diphosphite and 1,3,5-tris(4-tert-butyl-3-hydroxy-2,6-dimethylphenyl)-1,3,5-triazine-2,4,6-(1H,3H,5H)-trione, with a mass ratio of 1:1.2.

[0095] The high-efficiency degassing agent is MPP620 (MPI, American Micro Powder Company).

[0096] Comparative Example 4

[0097] This comparative example provides a method for preparing an enhanced POE photovoltaic encapsulation film, which comprises the following steps:

[0098] 100 parts by weight of POE resin, 15 parts by weight of polyethylene fiber, 15 parts by weight of reinforcing resin, and 5 parts by weight of compatibilizer are mixed evenly, and then added with 0.05 parts by weight of coupling agent, 2.1 parts by weight of cross-linking agent, 0.05 parts by weight of antioxidant, 0.05 parts by weight of UV absorber, 0.15 parts of high-efficiency degassing agent, and 40 parts of thermal conductive powder, and put into an extruder for mixing. The extruder temperature is 140°C, and the film is formed through casting, embossing, and cooling.

[0099] The thermal conductive powder is a mixture of nano zinc oxide and aluminum nitride, with a mass ratio of 2.5:1.

[0100] The length of polyethylene fiber is 0.5-40μm, the thermal conductivity is 80-100W / m·k, and the molecular weight of polyethylene is above 1 million;

[0101] The reinforcing resin is a mixture of reinforcing resin polybutene and ethylene propylene rubber, with a mass ratio of 1:1;

[0102] The compatibilizer is a mixture of POE grafted methacrylate copolymer, polypropylene grafted glycidyl methacrylate copolymer and EPDM grafted maleic anhydride copolymer, with a mass ratio of 1:1.2:2.5;

[0103] The coupling agent is a mixture of γ-aminopropyltriethoxysilane and methacrylate silane in a mass ratio of 1:1;

[0104] The crosslinking agent is a mixture of tert-amyl peroxybenzoate and 2,2-bis(tert-amylperoxy)-butane in a mass ratio of 1:1.2;

[0105] The antioxidant is a mixture of pentaerythritol distearate diphosphite and 1,3,5-tris(4-tert-butyl-3-hydroxy-2,6-dimethylphenyl)-1,3,5-triazine-2,4,6-(1H,3H,5H)-trione, with a mass ratio of 1:1.5;

[0106] The high-efficiency degassing agent is MPP620 (MPI, American Micro Powder Company).

[0107] Comparative Example 5

[0108] This comparative example provides a method for preparing an enhanced POE photovoltaic encapsulation film, which comprises the following steps:

[0109] 100 parts by weight of POE resin, 18 parts by weight of polyethylene fiber, 18 parts by weight of reinforcing resin, and 6 parts by weight of compatibilizer are mixed evenly, and then added with 0.06 parts by weight of coupling agent, 4 parts by weight of cross-linking agent, 0.06 parts by weight of antioxidant, 0.02-0.08 parts by weight of UV absorber, 0.16 parts of high-efficiency degassing agent, and 40 parts of thermal conductive powder, and put into an extruder for mixing. The extruder temperature is 140°C, and the film is formed through casting, embossing, and cooling.

[0110] The thermal conductive powder is a mixture of nano zinc oxide and aluminum nitride, with a mass ratio of 2.5:1.

[0111] The length of polyethylene fiber is 0.5-40μm, the thermal conductivity is 80-100W / m·k, and the molecular weight of polyethylene is above 1 million;

[0112] The reinforcing resin is a mixture of reinforcing resin polybutene and ethylene propylene rubber, with a mass ratio of 1:1;

[0113] The compatibilizer is a mixture of POE grafted methacrylate copolymer, polypropylene grafted glycidyl methacrylate copolymer and EPDM grafted maleic anhydride copolymer, with a mass ratio of 1:1.2:2.5;

[0114] The coupling agent is a mixture of γ-aminopropyltriethoxysilane and methacrylate silane in a mass ratio of 1:1;

[0115] The crosslinking agent is a mixture of tert-amyl peroxybenzoate and 2,2-bis(tert-amylperoxy)-butane in a mass ratio of 1:1.2;

[0116] The antioxidant is a mixture of pentaerythritol distearate diphosphite and 1,3,5-tris(4-tert-butyl-3-hydroxy-2,6-dimethylphenyl)-1,3,5-triazine-2,4,6-(1H,3H,5H)-trione, with a mass ratio of 1:1.5;

[0117] The high-efficiency degassing agent is MPP620 (MPI, American Micro Powder Company).

[0118] The performance of the photovoltaic encapsulation films prepared in Comparative Examples 2-5 was tested below, and the relevant experimental results are shown in Table 3.

[0119] Table 3. Performance test results of photovoltaic encapsulation films prepared in Comparative Examples 2-5

[0120] project Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Crosslinking degree (%) 82 84 86 85 Tensile strength (MPa) >17 >18 >19 >18 Light transmittance >91 >92 >93 >90 Glass bonding strength (N / cm) >82 >86 >89 >89

[0121] It can be seen from the experimental results in Table 3 that the tensile strength and light transmittance of the enhanced POE photovoltaic encapsulation films prepared in Comparative Examples 2-5 by adding reinforcing resin and compatibilizer are not as good as those of Examples 1-2 of the present invention.

Claims

1. A multi-layer co-extruded POE photovoltaic encapsulation film, wherein: The photovoltaic encapsulation film comprises three layers, namely an upper layer, a middle layer and a lower layer; the upper layer and the lower layer are both EVA layers, and the middle layer is a POE layer; The EVA layer contains 30-35% vinyl acetate and a density of 0.920-0.948 g / cm 3 , MFI is 1.5-15g / 10min; The raw materials of the POE layer include: 100 parts by weight of POE resin, 5-30 parts by weight of polypropylene fiber, 0.1-5 parts by weight of a cross-linking agent, 0.01-2 parts by weight of a coupling agent, and 0.01-0.8 parts by weight of an antioxidant; The octene content of the POE resin is 20-35%, and the density of the POE resin is 0.875-0.890 g / cm 3 , MFI is 4-6g / 10min.

2. The photovoltaic encapsulation film according to claim 1, wherein: The added amount of the polypropylene fiber is 10 to 20 parts by weight, the added amount of the crosslinking agent is 0.1-1 part by weight, the added amount of the coupling agent is 0.05-0.1 part by weight, and the added amount of the antioxidant is 0.01-0.05 part by weight.

3. The photovoltaic encapsulation film according to claim 1 or 2, wherein: The polypropylene fiber has a length of 1-60 μm, a thermal conductivity of 0.25-100 W / m·k, a relative density of 0.90-0.92, and an intrinsic viscosity of 1.3-3.

4. The photovoltaic encapsulation film according to claim 1 or 2, wherein: The cross-linking agent includes: tetraisocyanate, propylene diamine, polyethylene glycol, polypropylene glycol, trimethylolpropane, trimethylolethane, polypropylene glycol glycidyl ether, p-toluenesulfonic acid, p-toluenesulfonyl chloride, 1,4-butylene glycol diacrylate, ethylene glycol dimethacrylate, butyl acrylate, dicumyl peroxide, bis-2,4-dichlorobenzoyl peroxide, 2,2-bis(tert-amylperoxy)-butane, tert-amyl perbenzoate, aluminum isopropoxide, zinc acetate, titanium acetylacetonate, acrylic acid, hydroxyethyl acrylate, hydroxypropyl acrylate, methacrylic acid, hydroxyethyl methacrylate, hydroxypropyl methacrylate, divinylbenzene, N-hydroxymethyl acrylamide, diacetone acrylamide, one or a combination of two or more thereof.

5. The photovoltaic encapsulation film according to claim 1 or 2, wherein: The coupling agent includes γ-aminopropyltriethoxysilane, γ-(2,3-epoxypropoxy)propyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane, n-octyltriethoxysilane, vinyltriethoxysilane, vinyltrimethoxysilane, vinyl-tri(2-methoxyethoxy)silane, isopropyl dioleyloxy (dioctylphosphoacyloxy) titanate, isopropyl trioleyloxy titanate, isopropoxy tris(dodecylbenzenesulfonyloxy) titanate, isopropoxy tris(dioctylpyrophosphate) titanate, bis(dioctylpyrophosphate) ethylene titanate, an ammonium salt aqueous solution of bis(dioctylpyrophosphate) ethylene titanate, tetraisopropyl di(dioctyl phosphite) titanate, isopropyl tristearate titanate, and methacrylate silane, or a combination of two or more thereof.

6. The photovoltaic encapsulation film according to claim 1 or 2, wherein: The antioxidant includes one or a combination of two or more of tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]pentaerythritol, β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, N,N'-hexane-1,6-diylbis[3-(3,5-di-tert-butyl-4-hydroxyphenylpropionamide)], 3,3',3',5,5',5'-hexa-tert-butyl-α,α',α'-(mesitylene-2,4,6-triyl)tri-p-cresol, and 2,6-di-tert-butyl-4-[4,6-bis(octylthio)-1,3,5-triazin-2-ylamino]phenol.

7. The photovoltaic encapsulation film according to claim 1, wherein: The thickness of the photovoltaic encapsulation film is 0.1-1 mm.

8. The photovoltaic encapsulation film according to claim 1, wherein: The thickness ratio of the upper layer, the middle layer and the lower layer is 0.7-1:1.8-2.1:0.7-1.

9. The method for preparing the multi-layer co-extruded POE photovoltaic encapsulation film according to any one of claims 1 to 8, wherein: The preparation method comprises: (1) POE resin and polypropylene fiber are uniformly mixed, and then extruded into granules at 180-250° C., and the obtained granules are uniformly mixed with a cross-linking agent, a coupling agent and an antioxidant to obtain the raw material of the middle layer; (2) mixing 100 parts by weight of EVA resin, 0.1-2 parts by weight of antioxidant, and 1-5 parts by weight of light stabilizer to obtain raw materials for the upper layer and the lower layer; (3) The raw materials of the upper layer, the middle layer and the lower layer are stirred and mixed in a mixing kettle at 45°C, added into respective feed barrels, melted and plasticized at a temperature of 180-250°C through an extruder, and fused at the co-extrusion grinding head at the flute of the extruder. After cast or calendering, embossing, cooling, pulling and winding, a multi-layer co-extruded POE photovoltaic encapsulation film is obtained.

10. The preparation method according to claim 9, wherein The light stabilizer includes one or a combination of two or more of bis(1-octyloxy-2,2,6,6-tetramethyl-4-piperidinyl) sebacate, poly-{[6-[(1,1,3,3-tetramethylbutyl)-imino]-1,3,5-triazine-2,4-diyl][2-(2,2,6,6-tetramethylpiperidinyl)-nitro-hexamethylene-[4-(2,2,6,6-tetramethylpiperidinyl)-nitro]], bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate, and poly(4-hydroxy-2,2,6,6-tetramethyl-1-piperidinethanol) succinate.

11. The preparation method according to claim 9, wherein In step (2), the antioxidant is a mixture of pentaerythritol distearate diphosphite and 1,3,5-tris(4-tert-butyl-3-hydroxy-2,6-dimethylphenyl)-1,3,5-triazine-2,4,6-(1H,3H,5H)-trione, with a mass ratio of 1:1-2.

Citation Information

Patent Citations

  • Packaging adhesive film for cross-linked POE (polyolefin elastomer) solar photovoltaic module

    CN103289582B

  • Photovoltaic packaging material POE adhesive film capable of resisting potential induced degradation (PID)

    CN109810639A

Cited By

  • Anti-radiation photovoltaic packaging adhesive film, preparation method thereof and photovoltaic module

    CN121950194A

  • Anti-radiation photovoltaic encapsulation adhesive film, preparation method thereof and photovoltaic module

    CN121950194B